Influence of Worldwide University Rankings on the Strategic Planning of Public Institutions in Thailand - Jiacheng Zhong; Yaoping Liu; Pharatt Run; Rong Xiong; Junaidi Junaidi (Ianna Journal of Interdisciplinary Studies)
Background: Due to the intense competition that both public and private higher education institutions face, academic administration and strategic planning have gained importance in recent years. Among these are the demands for resilience, sustainability, identity, and quality.